New-England historical and genealogical register. - Waters, Henry F.; New England Historic Genealogical Society ([Boston] : [New England Historic and Genealogical Society], 1892)
Vols. 37 (1883)-v. 52 (1898) include section: Genealogical gleanings in England, by H.F. Waters. Cf. NUC, pre-1956 imprints.
Title from caption.
Editors: 1876-Jan. 1901, J.W. Dean.--Apr. 1901-Oct. 1907, H.E. Woods.--1908-12, F.A. Foster.--1913- H.E. Scott.
Vols. 54-77 include annual supplement to April no.: Proceedings of the New-England Historic Genealogical Society at the annual meeting, 1900-23. Beginning in 1924, Proceedings are incorporated into the Apr. no. Cf. NUC, pre-1956 imprints.
Microfilm.
Keywords: New England -- History -- Periodicals; New England -- Genealogy -- Periodicals; New England; Genealogy; History; Periodicals; Periodicals; Genealogy